The Joint Practice of Conceptual History and the Study of Political Thought: Kari Palonen in Conversation with Rosario López and José María Rosales - Kari Palonen; Rosario López; José María Rosales (Scienza & Politica, 2024)
Kari Palonen’s work has remained an inspiration for conceptual and intellectual historians as well as for political theorists over the years. His career and contributions make him an ideal interlocutor for a conversation on the joint practice of conceptual history and the study of political thought. This interview, conducted by Rosario López and José María Rosales, took place as one of the sessions of the online seminar On the Joint Practice of Conceptual History and the Study of Political Thought, organized by Concepta: Research Seminars in Conceptual History and Political Thought on 8 and 9 January 2024.